Tinjauan Fikih Muamalah terhadap Praktik Jual Beli Pala Borongan di Pesantren Hidayatullah Kabupaten Fakfak Provinsi Papua Barat - Dede Rifaldy Ambar; Panji Adam; Shindu Irwansyah (Bandung Conference Series: Sharia Economic Law, 2022)
Abstract. The buying and selling of nutmeg between the Hidaytullah Islamic Boarding School Board and the dealer in Fakfak Regency is carried out on a wholesale basis. In this case, the pesantren sells nutmeg to the dealer who is still not ready to harvest which is still on the tree so that the suspended nutmeg changes in terms of weight and quality. Based on the discussion in the background of the problem above, the purpose of this study is to find out the practice of buying and selling nutmeg by Santri Cultivators of nutmeg at the Hidayatullah Islamic Boarding School, Fakfak Regency, and to find out the fiqh muamalah analysis of the practice of buying and selling nutmeg at the Hidayatullah Islamic Boarding School, Fakfak Regency. The research method used in the preparation of this research is to use a descriptive analytical method. The results showed that first, the sale and purchase of nutmeg at the Hidaytullah Fakfak Islamic Boarding School was done in cash, where the dealer paid cash to the pesantren, but the collection of nutmeg was suspended for a certain period. Second, from the madhiyah aspect, the sale and purchase is legal according to muamalah fiqh because the pillars and conditions of buying and selling have generally been met, but from the adabiyah aspect the buying and selling practice contains elements of dzalim actions where the Islamic boarding school is burdened with caring for the nutmeg that is still on the tree that has become property of dealer. Keywords: Buying and Selling, Nutmeg, Wholesale, and Muamalah Fiqh.Abstrak. Jual beli pala antara Pengurus Pesantren Hidaytullah dengan bandar di Kabupaten Fakfak dilakukan secara borongan. Dalam hal ini, pihak pesantren menjual pala kepada bandar yang masih masih ada pada pohonnya sehingga pala yang masih memungkinkan mengalami perubahan kualitas buah dan berat bersihnya. Berdasarkan pembahasan dalam latar belakang masalah di atas, maka tujuan penelitian adalahuntuk mengetahui praktek jual-beli pala yang dilakukan Santri Penggarap pala di Pesantren Hidayatullah Kabupaten Fakfak, dan untuk mengetahui analisis fikih muamalah terhadap praktek jual-beli pala yang dilakukan di Pesantren Hidayatullah Kabupaten Fakfak. Metode penelitian yang digunakan dalam penyusunan penelitian ini adalah dengan menggunakan metode deskriptif analitis. Hasil penelitian menunjukkan bahwa Pertama, pelaksanaan jual beli pala di Pesantren Hidaytullah Fakfak dilakukan secara tunai, dimana pihak bandar membayar tunai kepada pihak pesantren, namun pengambilan buah pala ditangguhkan pada masa tertentu. Kedua dari aspek madhiyah jual beli tersebut sudah sah menurut fikih muamalah karena rukun dan syarat jual beli secara umum telah terpenuhi, namun dari aspek adabiyah praktek jual beli tersebut mengandung unsur tindakan dzalim dimana pihak Pesantren terbebani perawatan pala yang masih ada pada pohon yang sudah menjadi milik bandar.Kata Kunci: Jual Beli, Pala, Borongan, dan Fikih Muamalah.